2017
DOI: 10.1021/acs.organomet.7b00755
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of a Dimeric Iminophosphorane Stabilized Zinc Carbene: (ZnCR2)2

Abstract: Single deprotonation of the bis­(iminophosphorano)­methane ligand (PhNPPh2)2CH2 (5-H2) with 1 equiv of p-tBu-benzylpotassium followed by reaction with zinc­(II) chloride led to the formation of the homoleptic complex ((PhNPPh2)2CH)2Zn, (5-H)2Zn. Deprotonation of 5-H2 with 2 equiv of p-tBu-benzylpotassium gave known potassium compound (5-K2)2 which reacted further with zinc­(II) chloride to the dimeric carbene complex [(PhNPPh2)2CZn]2 ((5-Zn)2). Crystal structures of (5-H)2Zn and (5-Zn)2 are compared to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In addition to the reactions with NC ligands, recent work revealed that excess nitrene radicals can also attack surface atoms of II–VI core/shell QDs, introduce surface traps, and degrade the luminescent properties. ,, The effect of undesirable nitrene radical attack may be worsened for shell-free perovskite NCs with labile ligands and a strong tendency to produce surface vacancies. In comparison, carbenes are more benign and have been adopted to passivate surface traps in QDs. , A tentative explanation for such a contrast between nitrene and carbene radicals can be traced to their difference in Lewis acidity/basicity. Both nitrene and carbene radicals are amphiphilic in terms of Lewis acidity/basicity .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the reactions with NC ligands, recent work revealed that excess nitrene radicals can also attack surface atoms of II–VI core/shell QDs, introduce surface traps, and degrade the luminescent properties. ,, The effect of undesirable nitrene radical attack may be worsened for shell-free perovskite NCs with labile ligands and a strong tendency to produce surface vacancies. In comparison, carbenes are more benign and have been adopted to passivate surface traps in QDs. , A tentative explanation for such a contrast between nitrene and carbene radicals can be traced to their difference in Lewis acidity/basicity. Both nitrene and carbene radicals are amphiphilic in terms of Lewis acidity/basicity .…”
Section: Resultsmentioning
confidence: 99%
“…The “closed shell” structure and the substitution with aryl and trifluoromethyl groups endow the carbene radicals with appreciable Lewis basicity . Some reports also used carbenes as Lewis bases/ligands to stabilize Cd 2+ or Zn 2+ metal complexes. , According to previous reports, a main source for surface defects on perovskite NCs is the halogen vacancy and uncoordinated metal sites (Lewis acidic). Carbene radicals with Lewis basicity are thus more benign to NC surface sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reduced PLQYs can be further related to the increased density of surface defects during the patterning stages, as indicated by the increased nonradiative recombination rates (Table S1). By contrast, carbenes have been reported as Lewis bases/ligands that are able to stabilize Cd 2 + or Zn 2 + -metal complexes [20] and passivate II-VI QDs. [21] Unraveling the nature of the photochemical effects of nitrene-and carbene-based crosslinkers needs further studies.…”
Section: Forschungsartikelmentioning
confidence: 99%